An investigation of snakebite antivenom usage in Taiwan - Chih-Chuan Lin (Journal of the Formosan Medical Association, 2016)
Four types of antivenom are used to treat snakebites by the six species of venomous snakes native to Taiwan. Research into antivenom use in Taiwan and its outcomes, as well as the utility of current Taiwan Poison Control Center guidelines for antivenom use, has been limited. We aimed to provide increased understanding by investigating the treatment and outcomes of patients treated for snakebite in Taiwan. Methods: On the basis of data collected from the 2009 Taiwan National Health Insurance database, patients with snakebites were identified and categorized into two sets of groups according to types of antivenom administered. The relationships between antivenom types, dosage and the variables of antibiotic use, surgical intervention, acute respiratory failure acute, renal failure, antivenom-related allergic reaction, mortality, need for hospital admission, and length of hospitalization were analyzed by multivariate logistic regression and the Kruskal–Wallis test. Results: The majority of patients were successfully treated by administration of 1 vial of antivenom and discharged without complications. However, patients treated for neurotoxic-type venom snakebite required administration of larger doses of antivenom and > 30% required surgical intervention, particularly those treated for Chinese cobra snakebite. Approximately 10% of patients were administered two types of antivenom. Conclusion: The results partially support Taiwan Poison Control Center guidelines for treating the hemorrhagic-type venom snakebite. However, deficit in the guidelines for treatment of neurotoxic-type venom snakebite is obvious and new guidelines for treatment of neurotoxic-type venom snakebite and diagnosis should be developed.